Franz von Zeiller und das Strafrecht - Christian Neschwara (Journal on European History of Law, 2024)
Franz Zeiller is considered one of the most influential jurists in Austria, particularly known for his contributions to legislation. As the editor of the ABGB (General Civil Code) in 1811, he made a lasting impact by providing commentaries that served as authentic references for legal practice. His second major work, the Criminal Code of 1803, also had remarkable longevity and influenced criminal legislation beyond Austria. Zeiller's approach to legislation aimed to ensure maximum security while minimising restrictions on individual freedom. His proposals for revising the criminal law in 1823 emphasised adapting laws to changing circumstances and considering practical experience, scientific progress, and cultural development. This article explores Zeiller's achievements, including his work on the ABGB and the Criminal Code of 1803 and the subsequent revisions and discussions surrounding his proposals.